2015
DOI: 10.1016/j.cjca.2015.07.619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Equivalence of Evolocumab Among Patient Subgroups in Proficio: A Pooled Analysis of 3146 Patients From Phase 3 Studies

Abstract: The acute technical success was reported as 94% for AVNRT, 88% for AVRT, 75% for atrial tachycardia, 97% for atrial flutter, and 97% for atrial fibrillation. The overall complication rate of any severity was 10%. Most of the complications related to atrial fibrillation ablation were captured later during the follow up visits. In AVRT, ventricular tachycardia and atrial flutter, complications developed mainly during the peri-procedural period. The chronic success (reported as success at last follow-up visit) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Goal achievement in patients with diabetes was high, with 87–88% of patients achieving LDL‐C levels below 1.8 mmol l –1 (70 mg dl −1 ) . A second pooled analysis of four Phase 3 trials also found that evolocumab reduced LDL‐C to a similar extent in patients with and without type 2 diabetes .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Goal achievement in patients with diabetes was high, with 87–88% of patients achieving LDL‐C levels below 1.8 mmol l –1 (70 mg dl −1 ) . A second pooled analysis of four Phase 3 trials also found that evolocumab reduced LDL‐C to a similar extent in patients with and without type 2 diabetes .…”
Section: Resultsmentioning
confidence: 95%
“…Finally, a pooled analysis of four Phase 3 studies found that evolocumab reduced LDL‐C regardless of age, gender, presence of metabolic syndrome and cardiovascular risk level .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with mixed dyslipidemia who were treated with evolocumab 140 mg every 2 weeks (Q2W) or 420 mg once every month (QM) from three completed phase 3 evolocumab trials of 12-week duration were included in the analysis [ 31 33 ]. Evolocumab biweekly and monthly doses have shown clinical equivalence [ 34 ]. The MENDEL-2 trial evaluated the safety and efficacy of evolocumab monotherapy versus placebo or ezetimibe on LDL-C reduction in patients with a 10-year Framingham risk score of ≤ 10% (NCT01763827) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%